2005
DOI: 10.1074/jbc.m411390200
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the Binding Site for Haptoglobin on Apolipoprotein A-I

Abstract: Haptoglobin (Hpt) was previously found to bind the high density lipoprotein (HDL) apolipoprotein A-I (ApoA-I) and able to inhibit the ApoA-I-dependent activity of the enzyme lecithin:cholesterol acyltransferase (LCAT), which plays a major role in the reverse cholesterol transport. The ApoA-I structure was analyzed to detect the site bound by Hpt. ApoA-I was treated by cyanogen bromide or hydroxylamine; the resulting frag

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 58 publications
(44 reference statements)
2
90
0
Order By: Relevance
“…Hp is an HDL-associated protein in humans. Hp has been shown by some but not all investigators to be an HDL-associated protein (24,(27)(28)(29). Critical analysis of these prior studies suggested that the key difference in these studies was in the manner in which the HDL was prepared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hp is an HDL-associated protein in humans. Hp has been shown by some but not all investigators to be an HDL-associated protein (24,(27)(28)(29). Critical analysis of these prior studies suggested that the key difference in these studies was in the manner in which the HDL was prepared.…”
Section: Resultsmentioning
confidence: 99%
“…A binding site for Hp on ApoA1 (amino acid residues 141-164) has been identified (27). Interestingly, lecithin acyl transferase (LCAT), whose activity is dependent on its binding to ApoA1, binds to ApoA1 residues 159 -170 (34).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Hp is synthesized by adipocytes as well as by hepatocytes, 9 and Hp locus is close to the loci of lipid-related enzymes such as lecithin:cholesterol acyltransferase and cholesteryl ester transfer protein. 20 Moreover, Hp is attached to high-density lipoproteins (HDL) and apolipoproteins (apo) such as apoA-I 24 and apoE 4 in humans, and to HDL and very high-density lipoproteins in cows. 12 Significant increases in Hp appeared in fasted goats at the same time as the clinical signs in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…106 This has been attributed to elevated levels of haptoglobin in these individuals that bind to apoA-I and reduce its availability for the LCAT reaction. 107 LCAT activity is also decreased in chronic renal disease, 108 possibly as a consequence of reduced transcription of the LCAT gene in the liver.…”
Section: Regulation Of Spherical Hdl Biogenesis In Disease Statesmentioning
confidence: 99%